Reflection seismology : theory, data processing, and interpretation - Yang, Wencai, 1942- (Elsevier, 2013)
Authored by a geophysicist with more than 50 years of experience in research and instruction, Reflection Seismology: Theory, Data Processing and Interpretation provides a single source of foundational knowledge in reflection seismology principles and theory. Reflection seismology has a broad range of applications and is used primarily by the oil and gas industry to provide high-resolution maps and build a coherent geological story from maps of processed seismic reflections. Combined with seismic attribute analysis and other exploration geophysics tools, it aids geologists and geo-engi.